Highly diastereoselective 1,3-dipolar cycloaddition of a D-galactose-derived nitrone with dimethyl maleate: synthesis of polyhydroxylated perhydroazaazulenes - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D. (Synlett, 2009)
An intermolecular 1,3-dipolar cycloaddition of a D-galactose-derived nitrone with dimethyl maleate was found to be perfectly diastereoselective at the nitrone carbon to give exclusive formation of isoxazolidine. The N-O bond reductive cleavage in isoxazolidine followed by lactam reduction afforded a pyrrolidine ring skeleton with sugar appendage that on acetonide cleavage and reductive amino-cyclization gave hitherto unknown hydroxymethyl-substituted hexa- and pentahydroxy perhydroazaazulenes.
Keywords: 1; 3-dipolar nitrone olefin cycloaddition (DNOC); diastereoselectivity; Iminosugars; inhibitors; nitrone

Stereo-controlled approach to pyrrolidine iminosugar C-glycosides and 1,4-dideoxy-1,4-imino-L-allitol using a D-mannose-derived cyclic nitrone - Bande, Omprakash P.; Jadhav, Vrushali H.; Puranik, Vedavati G.; Dhavale, Dilip D.; Lombardo, Marco (Tetrahedron Letters, 2009)
Intramolecular N-alkylation of 2,3-O-isopropylidene-5-O-methanesulfonyl-6-O-t-butyldimethylsilyl-D-mann ofuranose-oxime 7 afforded a five-membered cyclic nitrone 9, which on N-O bond reductive cleavage followed by deprotection of -OTBS and acetonide functionalities gave 1,4-dideoxy-1,4-imino-L-allitol (DIA) 3. Addition of allylmagnesium chloride to nitrone 9 afforded alpha-allylated product 10a in high diastereoselectivity providing an easy entry to N-hydroxy-C1-alpha-allyl-substituted pyrrolidine iminosugar 4a after removal of protecting group, while N-O bond reductive cleavage in 10a afforded C1-alpha-allyl-pyrrolidine iminosugar 4b. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Cyclic nitrone; Enzyme inhibitors; Iminosugars; pyrrolidine

Synthesis and conformational study of chiral oxepines: the baylis-hillman reaction and RCM approach with sugar aldehyde - Jadhav, Vrushali H.; Bande, Omprakash P.; Pinjari, Rahul V.; Gejji, Shridhar P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Journal of Organic Chemistry, 2009)
The Baylis-Hillman reaction of 3-O-allyl-alpha-D-xylo-pentodialdo-1,4-furanose 3 afforded a diastereomeric mixture of D-gluco- and L-ido-configured alpha-methylene-beta-hydroxy esters 4a and 4b, respectively, in a ratio of 2:3. Reduction of the ester functionality in 4a/4b gave alcohols 5a/5b. The diene thus formed in 5a/5b was subjected to ring-closing metathesis (Grubbs' second-generation catalyst) to afford oxa-bicyclic ring system 6a/6b in high yield. Further manipulation of the aectonide functionality in 6a and 6b afforded new polyhydroxylated oxepines 1a/2a and 1b/2b, respectively. The (1)H NMR of oxepines 1a and 1b in D(2)O showed doubling of signals indicating their existence in two different rotamers/conformers. This fact was substantiated by calculating energetics of 1 and 2 conformers using the density functional theory and correlating the calculated (1)H NMR chemical shift pattern with that of the experimental spectra.

Synthesis of azepane and nojirimycin iminosugars: the sharpless asymmetric epoxidation of D-glucose-derived allyl alcohol and highly regioselective epoxide ring opening using sodium azide - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron-Asymmetry, 2010)
The Sharp less asymmetric epoxidation of D-glucose-derived ally! alcohol 4 afforded alpha- and beta-epoxides 5a and 5b in high stereoselectivity. The epoxide ring opening in 5a/5b was studied with different nucleophilic azido reagents, under various reaction conditions, and was found to be highly regioselective to give the preferential formation of 6-azido diol 6a/6b over 5-azido-diol 7a/7b. The 6-azido diol 6a/6b and 5-azido dial 7a/7b thus obtained were converted to the corresponding seven- and six-membered iminosugar, namely, azepane 1a/1b and 1-deoxy-nojirimycin 2a/2b. (C) 2010 Elsevier Ltd. All rights reserved.

Synthesis of eight-membered iminocyclitols from D-glucose - Jadhav, Vrushali H.; Bande, Omprakash P.; Puranik, Vedavati G.; Dhavale, Dilip D. (Tetrahedron, 2010)
The Baylis-Hillman reaction of 3-o-benzyl-alpha-d-xylo-pentodialdo-1,4-furanose 2 afforded a diastereomeric mixture of L-ido- and D-gluco-configurated alpha-methylene-beta-hydroxy esters 3a and 3b, respectively, in 1:1 ratio. Conjugate addition of benzyl amine on 3a gave adduct 4a as a major product while, addition of benzyl amine to 3b gave only one diastereomer 4b. Reduction of ester functionality in 4a/4b, opening of 1,2-acetonide functionality followed by reductive amino-cyclization under hydrogenation condition afforded azocanes 1c/1d in good yield. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Baylis-Hillman reaction; Conjugate addition; diastereoselectivity; Iminosugars

Biomass derived beta-cyclodextrin-SO3H as a solid acid catalyst for esterification of carboxylic acids with alcohols - Thombal, Raju S.; Jadhav, Amol R.; Jadhav, Vrushali H. (RSC Advances, 2015)
A novel beta-cyclodextrin-SO3H carbon based solid acid catalyst was prepared in a convenient and ecofriendly manner and was characterized using FTIR, PXRD, EDAX and NH3TPD to illustrate that the carbon material has been functionalized with -SO3H, -COOH and -OH groups. The catalyst was studied for esterification of various carboxylic acids and alcohols under solvent free conditions and showed excellent catalytic performance and gave good yields of esters in the range 78-99% at 70 degrees C. No solvent was used either for catalyst preparation nor for esterification reaction. The catalyst can be easily recovered by simple filtration and reused for subsequent three runs without any significant impact on yields of products. The main advantage of this methodology is easy and ecofriendly catalyst preparation, easy catalyst separation, practical simplicity, safe reaction conditions, recyclable catalyst and high product yields.

Synthesis of (+/-) debenzoyl analogs of norsampsones as potential anticancer agents - Jadhav, Amol R.; Thombal, Raju S.; Nigam, Preeti; Jadhav, Vrushali H. (Tetrahedron Letters, 2015)
Synthesis of (+/-) debenzoyl analogs of norsampsones 1 and 2 is reported starting from commercially available 1,3-cyclohexadione in six steps with overall yields of 37% and 36%, respectively. Compounds 1 and 2 were tested for their anticancer activity and showed moderate anticancer activity against HeLa cell lines. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Acylphloroglucinols; Anticancer; Debenzoyl; Norsampsones

Total synthesis of the natural product EBC-329 - Thombal, Raju S.; Jadhav, Vrushali H. (Organic & Biomolecular Chemistry, 2015)
The first total synthesis of an anti-leukemic diterpene natural product EBC-329 (1) has been accomplished starting from readily available 6,6-dimethyl-3-oxabicyclo[3.1.0] hexane-2,4-dione (7). An efficient and general approach has been reported for the synthesis of EBC-329 in 13 steps with an overall yield of 10%.

Application of glucose derived magnetic solid acid for etherification of 5-HMF to 5-EMF, dehydration of sorbitol to isosorbide, and esterification of fatty acids - Thombal, Raju S.; Jadhav, Vrushali H. (Tetrahedron Letters, 2016)
In this study, the catalytic activity of Glu-Fe3O4-SO3H was evaluated for three acid catalyzed reactions: etherification of 5-hydroxymethylfurfural (5-HMF) to 5-ethoxymethylfurfural (5-EMF) in ethanol, dehydration of sorbitol to isosorbide, and esterification of fatty acids with good yields and selectivity. Moreover, the catalyst can be easily separated from the reaction with an external magnetic force and reused at least five times without a significant decrease in catalytic activity. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: dehydration; Esterification; etherification; Magnetic

Sulfonated graphene oxide as highly efficient catalyst for glycosylation - Thombal, Raju S.; Jadhav, Vrushali H. (Journal of Carbohydrate Chemistry, 2016)
Heterogeneous sulfonated graphene oxide for the first time has been used as a green and efficient catalyst for atom-economic glycosylation of unprotected, unactivated glycosyl donors or 2,3,4,6-tetra-O-acetylglycosyltrichloroacetimidate with various acceptors basically in the absence of solvent. The unprotected, unactivated glycosyl donors afforded mixtures of alpha- and beta-glycosides, while the 2,3,4,6-tetra-O-acetylglycosyltrichloroacetimidate afforded beta-glycosylated products with high yields and selectivity. The main advantages of this methodology are easy catalyst preparation, no need for dry reagents and reaction conditions, easy catalyst separation and recycling, and high product yields.
Keywords: glycol donor; glycosyl acceptor; glycosylation; reusability; Sulfonated graphene oxide

Efficient method for synthesis of 2,5-furandicarboxylic acid from 5-hydroxymethylfurfural and fructose using Pd/CC catalyst under aqueous conditions - Rathod, Pramod V.; Jadhav, Vrushali H. (ACS Sustainable Chemistry & Engineering, 2018)
Pd/CC catalyst was synthesized from readily available biomass-derived D-glucose. The catalyst was characterized using various techniques such as Fourier transform infrared spectroscopy, powder X-ray diffraction, energy dispersive X-ray analysis, scanning electron microscopy, C-13 cross polarization NMR, transmission electron microscopy, X-ray photoelectron spectroscopy, and Brunauer-Emmett-Teller (BET) surface area analysis. This catalyst showed excellent catalytic activity toward the synthesis of industrially important 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethylfurfural (HMF) and fructose. The process is simple, efficient, green, and industrially feasible. Oxidation of HMF proceeded in 85% yield, and dehydration of fructose followed by oxidation gave 64% yield of FDCA with 100% purity using Pd/CC catalyst and molecular O-2 as an oxidizing agent under aqueous reaction conditions. The one pot two step procedure is highly efficient for synthesis of FDCA from fructose as it avoids isolation of HMF and requires a single catalyst for two different steps. FDCA finds utility in next-generation bioplastic poly(ethylene 2,5-furandicarboxylate) (PEF), which is a replacement for fossil-fuel-based poly(ethylene terephthalate) (PET).

Transition-metal-free glucose-derived carbonaceous catalyst catalyzes direct C-H arylation of unactivated arenes with aryl halides - Jori, Popat K.; Jadhav, Vrushali H. (ChemistrySelect, 2019)
Transition metal free coupling reactions have gained lot of importance recently. The traditional method for the synthesis of biaryl's uses organometallic reagents for the arylation reactions. There are certain drawbacks associated with such traditional methods. Use of expensive metals, metal impurities in the products formed and disposal of metal waste generated are major problems that need to be taken care of. Thus, research has been focussed on using transition metal free catalyst for cross coupling reactions to encourage green environment and it still remains a challenge for researchers. Carbonaceous catalyst have attracted great attention recently as a heterogeneous catalyst as it has a carbon skeleton that is stable, easily separable, reusable, eco-friendly and highly economical compared to other heterogeneous catalyst. Carbonaceous catalysts have been studied in variety of organic reactions such as hydrolysis, dehydration, esterification, alkylation, condensation, oxathioketalization, dimerization, benzylation and trimethylsilylation, etc. It was estimated that - stacking interactions between carbonaceous catalyst and arenes will accelerate the coupling reaction. However to the best of our knowledge, there are no reports available in literature on use of carbonaceous catalyst for direct arylation of arenes. And thus, we developed a new method for C-H arylation of unactivated arenes with aryl halides using a transition metal free D-glucose derived carbonaceous catalyst.
Keywords: Arylation; carbonaceous; glucose; metal-free

Efficient synthesis of gamma-valerolactone-a potential fuel from biomass derived levulinic acid using catalytic transfer hydrogenation over Hf@CCSO3H catalyst - Jori, Popat K.; Jadhav, Vrushali H. (Catalysis Letters, 2020)
A new hafnium based carbonaceous catalyst (Hf@CCSO3H) was prepared by simultaneous carbonization and sulfonation of readily available glucose, followed by incorporation of hafnium metal on the surface of catalyst. The catalyst was well characterized using FT-IR, PXRD, EDX, SEM, C-13 CPNMR, XPS and BET analysis. The catalytic activity of Hf@CCSO3H was evaluated for synthesis of gamma-valerolactone-a potential fuel and green solvent. gamma-valerolactone was synthesized from biomass derived levulinic acid by catalytic transfer hydrogenation using 150 wt% of catalyst at 200 celcius for 24 h in isopropanol solvent as a hydrogen donor. 100% conversion of levulinic acid was achieved with an excellent yield of 96% with more than 99% selectivity of gamma-valerolactone as evident from GC analysis. The method developed is simple, efficient and economical. [GRAPHICS] .
Keywords: gamma-Valerolactone; Hydrogenation; levulinic acid; Transfer

Cobalt-immobilized carbon-based nano-catalyst for Csingle bondN cross coupling reaction - Bankar, Shubham R.; Kirdant, Swapnali P.; Jadhav, Vrushali H. (Results in Chemistry, 2022)
<span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/cross-coupling-reaction" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about cross coupling reaction from ScienceDirect's AI-generated Topic Pages">cross coupling reaction is very important in synthesis of pharmaceuticals, <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/occurrence-in-nature" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about natural products from ScienceDirect's AI-generated Topic Pages">natural products, <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/agrochemical" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about agrochemicals from ScienceDirect's AI-generated Topic Pages">agrochemicals, fine chemicals and functional materials. Traditionally, <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/palladium" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about palladium from ScienceDirect's AI-generated Topic Pages">palladium or copper metals are used for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling reaction. As palladium is expensive, we developed cobalt immobilized carbon-based nano-catalyst Co@CC for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling. In this work, we synthesized non-noble metal-based Co@CC nano-catalyst by <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/carbonization" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about carbonization from ScienceDirect's AI-generated Topic Pages">carbonization of glucose, it’s functionalization followed by immobilization of cobalt on the surface of the catalyst. The catalyst was well characterized. The C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N cross coupling reaction of various aryl <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/halide" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about halides from ScienceDirect's AI-generated Topic Pages">halides & amines using Co@CC nano-catalyst was optimized for solvent, reaction temperature & catalyst <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/concentration-condition" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about concentration conditions from ScienceDirect's AI-generated Topic Pages">concentration conditions. The catalyst showed high catalytic activity for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="box-sizing: border-box; margin: 0px; padding: 0px; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling of various aryl halides & amines to form aryl amines in good to excellent yield up to 91 % in <a class="topic-link" href="https://www.sciencedirect.com/topics/chemistry/sulfolane" style="box-sizing: border-box; margin: 0px; padding: 0px; background-color: transparent; word-break: break-word; text-decoration-thickness: 1px; text-decoration-color: rgb(46, 46, 46); color: rgb(46, 46, 46); text-underline-offset: 1px;" title="Learn more about sulfolane from ScienceDirect's AI-generated Topic Pages">sulfolane as a solvent at 150 °C. The catalyst showed recyclability up to 5 times. The method developed for C<img alt="single bond" src="https://sdfestaticassets-us-east-1.sciencedirectassets.com/shared-assets/55/entities/sbnd.gif" style="box-sizing: border-box; margin: 0px; padding: 0px; border-style: none; width: auto; max-width: 100%; height: auto; color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px; vertical-align: middle;" /><span style="color: rgb(46, 46, 46); font-family: ElsevierGulliver, Georgia, "Times New Roman", STIXGeneral, "Cambria Math", Arial, Helvetica, "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 16px;">N coupling reaction was noble metal free, ligand free, recyclable, sustainable, economical & environmentally friendly.

Highly efficient zirconium based carbonaceous solid acid catalyst for selective synthesis of 5-HMF from fructose and glucose in isopropanol as a solvent - Jori, Popat K.; Jadhav, Vrushali H. (Catalysis Letters, 2022)
A new zirconium based carbonaceous solid acid catalyst Zr@CC-PA with both Lewis and Bronsted acidic sites was prepared by simultaneous carbonization and phosphonation of glucose followed by incorporation of zirconium metal on the surface of the catalyst. The catalyst was easy to prepare and the synthesized catalyst was well characterized using different techniques such as FT-IR, P-XRD, EDAX, SEM, TEM and XPS analysis. The catalytic activity was evaluated for synthesis of a very important platform chemical 5-HMF from fructose to glucose using isopropanol as a solvent. The catalyst was found to be highly efficient giving 86% yield of 5-HMF from fructose and 45% yield from glucose with high selectively. The catalyst can be reused at least four times without depreciation in its catalytic activity. The catalytic method developed is efficient, green and economical.
Keywords: 5-Hydroxymethylfurfural; fructose; glucose; Zirconium based

Metal-free approach towards efficient synthesis of FDCA using a p-toluene sulfonic acid (p-TSA)-derived heterogeneous solid acid catalyst and oxone over two steps from HMF, fructose and glucose - Tamboli, Asma T. Biradar; Kirdant, Swapnali P.; Jadhav, Vrushali H. (New Journal of Chemistry, 2022)
In this work, a metal-free approach towards the synthesis of 2,5-furandicarboxylic acid (FDCA) from 5-hydroxymethylfurfural (HMF), fructose and glucose is reported over two steps using a p-toluene sulfonic acid (p-TSA)-derived heterogeneous solid acid catalyst (p-TSA-POM) in the first step and oxone as an oxidant in the second step. HMF, fructose and glucose were converted to 2,5-diformylfuran (DFF) using the p-TSA-POM catalyst followed by oxidation of DFF to FDCA using oxone. To the best of our knowledge, this is the first metal-free approach for the synthesis of FDCA directly from glucose. DFF was obtained from HMF in 91% yield, whereas it was obtained in 85% and 61% yields from fructose & glucose, respectively. DFF was further converted to FDCA using oxone as an oxidant. FDCA was obtained in an overall yield of 84%, 78% and 56% from HMF, fructose & glucose, respectively.

Recent developments in the applications of biomass-derived sulfonated carbonaceous solid acid catalysts - Kirdant, Swapnali P.; Tamboli, Asma T. Biradar; Jadhav, Vrushali H. (Helvetica Chimica Acta, 2022)
Recently, carbon-based materials are gaining a lot of attraction. It is considered as an emerging area of research and has gained significant importance as an efficient catalyst/material in various fields. Biomass is abundantly available, cheap and a renewable carbon resource. Sulfonated carbonaceous solid acid catalyst can be derived by sulfonation of various sources of biomass such as sugars, lignin, fruit waste, agro-waste, bio-char, etc. Sulfonated carbonaceous solid acid catalysts can be used as a substitute to liquid acids. These catalysts possess a stable carbon skeleton and are insoluble in almost all organic solvents as well as under acidic/basic conditions. This review covers details about biomass-derived sulfonated carbonaceous solid acid catalysts and its catalytic activities in many important transformations such as hydrolysis of cellulose, synthesis of biodiesel, synthesis of various important chemicals and for various organic transformations.
Keywords: Biodiesel; Biomass; cellulose; Hydrolysis; sulfonated carbonaceous solid acid catalyst

Green, practical & scalable approach towards the synthesis of valuable α-keto amides using a metal-free catalyst under solvent-free conditions - Bankar, Shubham R.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (New Journal of Chemistry, 2023)
alpha-Ketoamides are very important motifs as they are present in many natural products, drugs & biologically important molecules. We synthesized a very simple, cheap, eco-friendly & reusable glucose-based carbonaceous material (GCM), which showed high performance as a catalyst in the oxidative cross-dehydrogenative coupling (CDC) reaction of alpha-ketoaldehydes with amines for the synthesis of alpha-ketoamides. The GCM catalyst was also very efficient for one-pot two-step synthesis of alpha-ketoamides from alpha-ketoalcohols as well. The GCM catalyst was able to catalyze alcohol oxidation in alpha-ketoalcohols followed by CDC reaction with amines to form alpha-ketoalcohols. The reactions were found to proceed smoothly at a low temperature of 50 degrees C using a green & economical metal-free catalyst under base-free, ligand-free & solvent-free reaction conditions to get the corresponding alpha-ketoamides in good to excellent yields. The results demonstrated that the GCM catalyst showed acidic as well as superior oxidising catalytic activity due to the presence of a carboxylic acid (-COOH) and hydroxyl (-OH)-enriched carbonaceous framework, which enabled the synthesis of important alpha-ketoamide motifs. The applicability of the catalyst was also evaluated for the synthesis of an anti-HIV agent drug molecule. Greener, cheaper & eco-friendly GCM catalyst as well as catalytic process for synthesis of alpha-Keto Amides.

Alternative synthetic route for the pharmacophore of anticancer agent: triazolopyridazine derivative - Karche, Ranjit S.; Bankar, Shubham R.; Jadhav, Vrushali H. (Tetrahedron Letters, 2024)
ATAD2 has received attention as one of the potential oncogene with tumor-promoting aspects in many malignancies. ATAD2 is a highly conserved bromodomain family protein that exerts its biological functions by mainly AAA ATPase and bromodomain. Several small molecule inhibitors have been described in the literature. AZ13824374 (1) recently reported by Holt and co-workers showed promising in vitro (bio-chemical, cellular) and antiproliferative activity in range of breast cancer models. In this work, we described scalable synthetic route for triazolopyridazine derivative (2), a key intermediate of AZ13824374 (1) without using CO in the process. Triazolopyridazine helps to attain the bioactive conformation for AZ13824374 (1) through its crucial interaction with Tyr 1021 of ATAD2. Additionally, triazolopyridazine is extensively used as an intermediate for anticancer agents. This encouraged us to develop cost-effective and scalable process for it.
Keywords: Alternative process; Anticancer; Triazolopyridazine

Direct oxidation of alcohols to carboxylic acids using simple and economical Pd@Glu-HTC catalyst: practical and scalable approach towards biomass based value added chemicals - Kirdant, Swapnali P.; Bankar, Shubham R.; Jadhav, Vrushali H. (Biomass & Bioenergy, 2024)
Sustainable catalytic transformation of bio-based alcohols to high value-added fine chemicals is an important topic of research. This work described preparation of simple and economical Pd@Glu-HTC catalyst from biomass derived low cost D-glucose. Hydrothermal carbonization of glucose was carried out in first step to synthesize GluHTC support in a simpler, greener, economical and efficient manner followed by incorporation of palladium metal on surface of the catalyst in second step. The catalyst was characterized using techniques such as Fourier Transform Infrared Spectroscopy (FT-IR), Solid-state Cross-Polarization Magic Angle Spinning Carbon-13 (13C CPMAS), Energy-dispersive X-ray spectroscopy (EDAX), Powder X-ray diffraction (P-XRD), X-ray photoelectron spectroscopy (XPS), Thermogravimetric/Differential Thermal Analyzer (TG-DTA), Field emission scanning electron microscopy (FE-SEM) and High-resolution transmission electron microscopy (HR-TEM). The catalyst was evaluated for direct oxidation of alcohols to yield carboxylic acids and exhibited very good catalytic activity for wider substrate scope. Oxidation of alcohols was carried out using milder base, molecular oxygen and water as a solvent to achieve 92-99 % excellent yields. The practical utility of current strategy was also studied for gram scale synthesis of bio-based value added industrially important chemicals such as furoic acid (flavouring agent and preservative in industry), 2, 5-furan-dicarboxylic acid (monomer to 100 % fossil-free, recyclable polymer polyethylene furanoate (PEF), tetrahydro-2-furoic acid (production of many drugs) and vanillin (important product of flavor and fragrance industry). Pd@Glu-HTC catalyst was found to be reusable for four recycles and the catalytic performance was retained without any loss in its activity after four cycles.
Keywords: Bio-based chemicals; Carbonaceous catalyst; Carboxylic acid; Oxidation

Selective oxidation of biomass derived 5-hydroxymethylfurfural (HMF) to 2,5-diformylfuran (DFF) over spent dry cell battery cathode material (BCM-2) - Ghadge, Sambhaji S.; Bankar, Shubham R.; Jadhav, Vrushali H. (ACS Applied Engineering Materials, 2024)
Widespread use of batteries across the globe generates a huge amount of waste. This work is the first to report spent dry cell (Zn-Carbon) battery cathode material (BCM-2) as a heterogeneous catalyst for selective synthesis of fine chemical 2,5-diformylfuran (DFF). Cathode material was easily separated from spent batteries, and acid leached followed by calcination to obtain black powder that was denoted as BCM-2. The catalyst was characterized using various techniques such as P-XRD, EDAX, SEM, HR-TEM, TGA, XPS, and BET analysis. Superior catalytic activity was shown by the catalyst for selective formation of DFF using molecular O2 as a sole oxidant. The catalyst was found to give excellent HMF conversion of 97% with 98% high selectivity of DFF. The BCM-2 catalyst was easily recycled and reused without any significant loss in its catalytic activity. This is one of the best examples for a sustainable, cost-effective, and highly efficient catalytic system for the synthesis of the value-added chemical DFF.

Graphitic-C3N4/γ-Al2O3 composite catalyst for synthesis of 5-(Hydroxymethyl) furfural from d-Glucose - Kirdant, Swapnali P.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (Energy & Fuels, 2025)
Currently, the synthesis of 5-hydroxymethylfurfural (5-HMF), with high yields and selectivity from different renewable sources, is an important focus in the biomass conversion area. In the present study, a g-C3N4/gamma-Al2O3(1:1) composite catalyst was prepared using graphitic carbon nitride (g-C3N4) and acidic gamma-alumina (gamma-Al2O3), which was evaluated for its catalytic activity in converting sugars, mainly glucose, to 5-HMF. In the g-C3N4/gamma-Al2O3(1:1) catalyst, N-containing groups on g-C3N4 provided basicity and gamma-Al2O3 provided Lewis acidity to the catalyst. The g-C3N4/gamma-Al2O3(1:1) composite catalyst showed superior activity for 5-HMF synthesis compared to gamma-Al2O3 and g-C3N4 alone. The increased acidic and basic properties of the g-C3N4/gamma-Al2O3(1:1) catalyst significantly influenced both glucose-to-fructose isomerization and dehydration of fructose to HMF by increasing the yield of 5-HMF. In addition, the solvent DMSO:water also played an important role in the one-pot conversion of glucose to HMF by minimizing side reactions, which significantly improved the 5-HMF yield. The reaction was optimized for various solvents, temperatures, and catalyst concentrations to get a maximum yield of 91% from glucose with >99% selectivity of crude 5-HMF. Other sugars like fructose, sucrose, and lactose also provided good yields of 5-HMF. The g-C3N4/gamma-Al2O3(1:1) catalyst was stable and was effectively reused for up to four cycles.

Modification of some steps in the synthesis of Ivacaftor by mechano-chemical approach - Bankar, Shubham R.; Jadhav, Vrushali H. (Sustainable Chemistry for Climate Action, 2025)
<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">Recently implementation of the mechano-chemistry approach for carrying out some of the steps in the synthesis of API’s, is considered an attractive and environment friendly approach as it permits solvent-free reactions or the use of activators for the reaction, making the process efficient and economical. In this study, we focused on the modification of some steps in the drug Ivacaftor, which is one of the most expensive drugs in the market. For the first time, a mechano-chemical approach was employed to replace some steps in the synthesis of Ivacaftor. One of the fragment 5-amino-2,4-di‑tert‑butyl‑phenol (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">5<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) required in the synthesis of Ivacaftor was prepared in two steps from commercially available 2, 4-bis(1,1-dimethylethyl)-5-nitrophenyl methyl carbonate (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">6<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) by mechano-chemistry approach in good yields. In the last step, fragment 5-amino-2,4-di‑tert‑butyl‑phenol (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">5<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) was coupled with 4-quinolone-3-carboxylic acid <span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">(4)<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;"> using mechano-chemistry to obtain Ivacaftor (<span style="box-sizing: border-box; margin: 0px; padding: 0px; font-weight: bolder; color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">1<span style="color: rgb(31, 31, 31); font-family: ElsevierGulliver, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif, sans-serif; font-size: 16px;">) in good yields. The advantage of this methodology was it avoided the use of solvent in all three steps of ivacaftor synthesis, making the process efficient and economical.

Liquid-assisted grinding mechanochemical approach for direct amidation of pyridone-carboxylic acid to synthesize an intermediate used in anti-viral API's bictegravir and cabotegravir - Karche, Ranjit S.; Bankar, Shubham R.; Jadhav, Vrushali H. (ChemistrySelect, 2026)
Mechanochemistry is viewed as an appealing alternative for the synthesis of various compounds, since it is regarded as an eco-friendly and economical method that can be performed under solvent-free reaction conditions. In this work, neat grinding and liquid-assisted grinding (LAG) methods for direct amidation of pyridone-carboxylic acid and 2,4,6-trifluorobenzylamine/2,4-difluorobenzylamine were studied using EDC.HCl as a coupling reagent to synthesize important intermediates used in the synthesis of anti-HIV drug molecules bictegravir, cabotegravir, and dolutegravir. The products were easy to separate as they easily precipitated out from water, and the purity of the products obtained was similar to 97% for the intermediates, thus avoiding the need for their purification. This process eliminated the use of organic solvents for the reaction as well as for the work-up and product purification. The reaction was scaled up on a 15-g scale, giving good yields of the intermediates. The process was found to be practical, scalable, and reproducible on a gram scale.
Keywords: amidation; bictegravir; cabotegravir; mechanochemistry

One-pot tandem oxidative-wittig olefination of primary alcohols using spent battery material as a heterogeneous catalyst in green solvent GVL - Bankar, Shubham R.; Ghadge, Sambhaji S.; Jadhav, Vrushali H. (Catalysis Letters, 2026)
Extensive global utilization of dry cell batteries resulted in generation of huge amount of battery waste. Up-cycling of spent battery waste material as a heterogeneous catalyst is an emerging area of research. Cathode material from spent dry cell battery (Zinc-carbon) was isolated, acid leached and calcined to obtain BCM-2 which was used as a heterogeneous catalyst for one-pot tandem oxidative-Wittig olefination in & upsih;-valerolactone (GVL) a bio-based green solvent at a temperature of 50 degrees C. Reaction was found to proceed smoothly using an economical catalyst and environment friendly conditions to get olefins in good yield up-to 74%. The catalyst was found to be reusable for four cycles. The reaction was carried out two-steps in one pot using spent battery material as a catalyst in GVL as a solvent under mild reaction conditions and the applicability of catalyst was shown in 13 examples. The catalyst's effectiveness was also assessed in synthesis of (E)-3, 4 `, 5-trimethoxy-trans-stilbene, an intermediate for biologically active Resveratol.
Keywords: One-pot; Oxidation; Spent battery; Wittig olefination